Splitting Apart: How the Soviet-Albanian Relations Came to an End - Pilaca, Geri; Nako, Alban (Richtmann Publishing, 2021)
Albania was the only Eastern European country to exit from the Warsaw Pact and consequently become diplomatically isolated by its member states by late 1961. Such an event was the result of the continuous accusations exchanged between the Albanian and the Soviet Leaders, primarily between Enver Hoxha and Nikita Khrushchev. In the midst of the turbulent Soviet-Albanian relations, China offered its alliance to Albania which only worsened the situation. This study aims to illustrate how the curve of the Albanian-Soviet partnership changed over time, starting from the Stalin era and finishing with the Khrushchev era. More precisely, this study explains how Khrushchevâ€™s decision-making concerning other countries, especially Yugoslavia, pushed the Albanian leaders into changing attitude towards the Soviet Union and make alliances with Mao Zedong. Â Received: 4 May 2021 / Accepted: 21 June 2021 / Published: 8 July 2021